2010
DOI: 10.1093/bja/aep320
|View full text |Cite
|
Sign up to set email alerts
|

Small temperature variations alter edaravone-induced neuroprotection of cortical cultures exposed to prolonged hypoxic episodes

Abstract: Temperature is a potential factor in determining whether edaravone confers a neuroprotective effect when applied during prolonged hypoxic insults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…Mild hypothermia treatment for 24 h after OGD markedly relieves neuronal hypoxic and sugar-deficient injury caused by OGD, whereas mild hypothermia treatment for 6 h did not have a significant protective effect. These results suggest that mild hypothermia treatment after OGD requires application for a long duration, which is in agreement with previously reported research results (34,36,37). Therefore, for ischemic and hypoxic cerebral injury, mild hypothermia treatment for 24 h is more effective.…”
Section: Discussionsupporting
confidence: 92%
“…Mild hypothermia treatment for 24 h after OGD markedly relieves neuronal hypoxic and sugar-deficient injury caused by OGD, whereas mild hypothermia treatment for 6 h did not have a significant protective effect. These results suggest that mild hypothermia treatment after OGD requires application for a long duration, which is in agreement with previously reported research results (34,36,37). Therefore, for ischemic and hypoxic cerebral injury, mild hypothermia treatment for 24 h is more effective.…”
Section: Discussionsupporting
confidence: 92%
“…Edaravone, which has been used clinically in both ischemia and neurodegenerative diseases, confers neuroprotection in comparable concentrations to CeNPs in cell culture studies, but edaravone is not as potent an antioxidant. Neuroprotective effects in brain slices require 100–200 times higher concentrations of edaravone that CeNPs (5.8 μM CeNPs versus >500 μM edaravone) to achieve similar effects [83,84]. Based on the greater potency of CeNPs in these studies, CeNPs are an attractive candidate for further development as a therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that EDA protects neuronal cells from ischemic injury by inhibiting the translocation of 5-lipoxygenase to the nuclear membrane, thereby blocking the 5-lipoxygenase signaling pathway (12). Moreover, EDA combined with MH significantly improves neuroprotection in rats exposed to hypoxia (13).…”
Section: Introductionmentioning
confidence: 99%